ANALISIS WACANA: SURAT KARTINI â€HIDUP BARU BERBAHAGIA PULAâ€ DALAM KUMPULAN HABIS GELAP TERBITLAH TERANG KAJIAN ASPEK KOHESI DAN ASPEK KOHERENSI - , Dra, Rustiati (Widya Warta, 2012)
This study aimed to describe and explain the aspects of cohesion and coherence inÂ  Kartiniâ€™s letter"Hidup Baru Berbahagia Pula". The research is qualitativeÂ  descriptive in nature. The data of the research are sentences and paragraphs. They were taken from Kartiniâ€™s letter "Hidup Baru Berbahagia Pula", available in the collection ofÂ  â€œHabis Gelap Terbitlah Terangâ€. The data analysis showed that grammatical cohesion in the letter is markedÂ  by personal, demonstrative, andÂ  comparative references â€“ eitherÂ  anaphoric and cataphoric. Reference is dominantly used. Substitution applied is of twoÂ  kinds, namely demikian, whichÂ  is quite dominant and hal itu. Conjunction used is of five types, that is,Â  conjunctions indicating oppositional, additional,Â  conditional, causal, and concessive relationships. Lexical cohesion is marked by repetition, synonymy, and antonymy. Lexical cohesion here functions to facilitate intensity, respect,Â  variation of oppositional sentence,Â  meaning clarity, and impression of colourful writing. Coherence is marked byÂ  relationships of addition, paraphrase, identification, comparison, and cause-effect. The aspectsÂ  of cohesion and coherence in this case act to tie the parts of the discourse, so that a goodÂ  discourse results.